Selectivity Of Forest Tree Species For Debarking By Elephants In Rabongo Forest- Murchison Falls National Park, Uganda - Odoi, Juventine Boaz; Babweteera, Fred; Gwali, Samson; Tweheyo, Mnason (Researchjournali’s Journal of Ecology, 2016)
Selectivity of the different forest tree species for debarking by elephants in a forest ecosystem is an important phenomenon for understanding the interactions between the large herbivores and the woody community in the tropical forest ecosystem. Here we present a long term investigation on elephant preference to forest trees debarking in Rabongo Forest spanning 20 years since 1992 in seven (7) one hectare plots established in 1992 distributed over 46 hactare in Rabongo Forest which is an important habitat for most large herbivores in Murchison Falls National Park. Diospyros abyssinica; Holoptelea grandis; Trichilea prieuriana and Cynometra alexandri were the most debarked/preferred tree species and also the most abundant in the forest in Rabongo Forest although the number of the debarked trees ≥ 10cm dbh reduced by 4%. Synthesis. There should be close monitoring of the number of elephants that visit Rabongo Forest over the years to relate with the number of stems debarked over the years to guide on the need to maintain the right elephant carrying capacity for the forest. We also recommend for further investigation for what attributes make the above tree species be preferred by elephants in Rabongo Forest
Keywords: Debarking; Scars; Resilience; Selectivity; Preferences